2017
DOI: 10.2174/1567205014666170203153325
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β 5'-flanking DNA Methylation and Expression in Alzheimer’s Disease Patients

Abstract: These results point out that GSK3β hyperactivity, and then NFTs formation, could come into function at an early stage of the disease and then turn off at the last stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Among the kinases identified to be responsible for tau hyperphosphorylation, GSK-3β plays an important role in the pathological changes of tau protein in AD [ 23 ]. Data collected in humans show increased activation of GSK-3β in early-stage AD [ 24 ], while a consistent inhibition was observed in late-stage AD [ 25 , 26 ], thus suggesting that GSK-3β-mediated tau phosphorylation is among the earliest events during the progression of the pathology. Increasing evidence shows that tau in dendrites plays a key role in Aβ-induced detrimental effects.…”
Section: Introductionmentioning
confidence: 93%
“…Among the kinases identified to be responsible for tau hyperphosphorylation, GSK-3β plays an important role in the pathological changes of tau protein in AD [ 23 ]. Data collected in humans show increased activation of GSK-3β in early-stage AD [ 24 ], while a consistent inhibition was observed in late-stage AD [ 25 , 26 ], thus suggesting that GSK-3β-mediated tau phosphorylation is among the earliest events during the progression of the pathology. Increasing evidence shows that tau in dendrites plays a key role in Aβ-induced detrimental effects.…”
Section: Introductionmentioning
confidence: 93%
“…129 A further study identified hypomethylation of GSK3B in an in vitro experiment mimicking AD-related pathology and postmortem AD samples. 130 Intriguingly, only patients in the initial disease stage exhibited GSK3β upregulation. 130 A memory-enhancing gene, reelin (RELN), has also been highly implicated in AD.…”
Section: Neurochemical Processesmentioning
confidence: 99%
“…130 Intriguingly, only patients in the initial disease stage exhibited GSK3β upregulation. 130 A memory-enhancing gene, reelin (RELN), has also been highly implicated in AD. It was shown to bind apolipoprotein E receptor 2 (ApoER2) or verylow-density liporeceptor to facilitate the migration of neurons and synaptic transmission.…”
Section: Neurochemical Processesmentioning
confidence: 99%
“…Recently Martínez-Iglesias et al [354] analyzed the content of 5mC and 5hmC, and the expression of DNMT3a-responsible for de novo methylation [354] showing that global 5mC and 5hmC levels are significantly lower in AD mouse model as compared to healthy animals. Conversely, other studies reported no significant differences between healthy and AD brain samples [354], or even an increase of methylation and hydroxymethylation levels in different regions of the AD brain [354].…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 99%